Limb imaging of the Venus O2 visible nightglow with the Venus Monitoring Camera. Issue 11 (13th June 2013) - García Muñoz, A.; Hueso, R.; Sánchez‐Lavega, A.; Markiewicz, W. J.; Titov, D. V.; Witasse, O.; Opitz, A.
Abstract [1] We investigated the Venus O2 visible nightglow with imagery from the Venus Monitoring Camera on Venus Express. Drawing from data collected between April 2007 and January 2011, we study the global distribution of this emission, discovered in the late 1970s by the Venera 9 and 10 missions. The inferred limb‐viewing intensities are on the order of 150 kR at the lower latitudes and seem to drop somewhat toward the poles. The emission is generally stable, although there are episodes when the intensities rise up to 500 kR. We compare a set of Venus Monitoring Camera observations with coincident measurements of the O2 nightglow at 1.27 µm made with the Visible and Infrared Thermal Imaging Spectrometer, also on Venus Express. From the evidence gathered in this and past works, we suggest a direct correlation between the instantaneous emissions from the two O2 nightglow systems. Possible implications regarding the uncertain origin of the atomic oxygen green line at 557.7 nm are noted.